Comparative analysis of financial performance of Pharmaceutical Companies after the Covid-19 pandemic - Qotrun Nada, Zanuba; Yusuf, Furtasan Ali; Kenedi, Kenedi (Enrichment : Journal of Management, 2025)
This study aims to analyze and compare the financial performance of pharmaceutical companies in Indonesia in the post-COVID-19 pandemic period. This study is based on the phenomenon of increasing demand for pharmaceutical products during the pandemic, which significantly affected the company's revenue structure, profitability, and efficiency. With the end of the global health crisis, it is important to understand how the financial performance of pharmaceutical companies has changed and whether there have been adjustments to their business strategies in facing the new normal. The research method uses a quantitative approach with financial ratio analysis covering liquidity, profitability, solvency, and activity. Data are taken from the annual financial reports of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023, representing the periods before, during, and after the pandemic. Comparative analysis was conducted using different tests (paired sample t-test and ANOVA) to assess the significance of changes in performance between periods. The results show that in general, pharmaceutical companies experienced a significant increase in financial performance during the pandemic, particularly in profitability ratios. However, after the pandemic ended, there was a decline in revenue and profit margins due to the decline in demand for emergency health products. Nevertheless, several companies were able to maintain positive performance through product diversification and healthcare service innovation. These findings are relevant for corporate management, investors, and policymakers in understanding the dynamics of the pharmaceutical industry in the post-pandemic era and the adaptation strategies needed to maintain business sustainability amid fluctuating healthcare sector demand.